2017
DOI: 10.1016/j.apergo.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lane departure warnings onset and reliability on car drivers' behaviors

Abstract: Lane departures represent an important cause of road crashes. The objective of the present study was to assess the effects of an auditory Lane Departure Warning System (LDWS) for partial and full lane departures (onset manipulation) combined with missed warnings (reliability manipulation: 100% reliable, 83% reliable and 66% reliable) on drivers' performances and acceptance. Several studies indicate that LDWS improves drivers' performances during lane departure episodes. However, little is known about the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Therefore changes in driver performance due to errors in the LKAS may follow similar patterns to those for LDWS degradation. The influence of LDWS reliability on acceptance has been studied by Navarro et al (2017) in which reliable LDWS was found to improve the driver's steering behavior with more effective recovery maneuvers to lane departures. However, late or missing warnings caused the driver to perform similarly to having no warning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore changes in driver performance due to errors in the LKAS may follow similar patterns to those for LDWS degradation. The influence of LDWS reliability on acceptance has been studied by Navarro et al (2017) in which reliable LDWS was found to improve the driver's steering behavior with more effective recovery maneuvers to lane departures. However, late or missing warnings caused the driver to perform similarly to having no warning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…over the past few years, Advanced Driver Assistance Systems (ADAS) has emerged as an important research field to enhance automotive safety [1]. With the objective of traffic accidents avoidance, ADAS include a lane departure warning to alert drivers to take a corrective action when the vehicle tends to drift off a lane.…”
Section: Introductionmentioning
confidence: 99%
“…Different researchers have developed advanced assistance systems to alert the driver of a potential collision (Biondi, Strayer, Rossi, Gastaldi, & Mulatti, 2017;Lylykangas, Surakka, Salminen, Farooq, & Raisamo, 2016;Navarro et al, 2017). Schwarz and Fastenmeier (2017)) conducted a driving simulator study with 88 participants.…”
Section: Introductionmentioning
confidence: 99%